Nitrogen management in maize + soybean intercropping system in semi-arid condition of Kandahar, Afghanistan - Mumtaz Baryal; S.S. Rathore; Mukhtar Ahmad Faiz; Kapila Shekhawat (Annals of Agricultural Research, 2023)
A field experiment on "Nitrogen management in maize + soybean intercropping system"was carried during the summer season of 2017 at Kandahar, Afghanistan. The experiment was laid out in a split plot design with three replications. The main plots consisted of different system of intercropping of maize and soybean and the subplot included the nitrogen management treatments. The growth parameters of maize like plant height, dry matter accumulation and leaf area index in maize + one row of soybean were higher in intercropping system over sole maize, but maize + one row of soybean recorded markedly higher dry matter/plant at 60, and 90 DAS compared to sole maize. Nitrogen application significantly influenced the plant height, dry matter/plant at all the growth stages of crop growth, except at 30 DAS. Maize yield attributes (cobs/plant, length of cob and number of gains/cob) significantly higher under that maize + one row of soybean than those recorded in sole maize. Also, N application, up to 80 kg ha–1 markedly increased girth of cob and the number of cobs per plant while the application of 120 kg N ha–1 brought about only marginal increase. However, highest 1000-grain was recorded in maize + two row of soybean. However, 1000-grain weight increased with increasing rates of N up to 120 kg ha–1. Maize grain yield increased under intercropping maize + one row of soybean significantly higher grain, stover and biological yield over sole maize. Application of N at increasing rates brought about a significant increase in grain yield of maize from control to 80 kg ha–1.